Neuropsychology and electroencephalography to study attention deficit hyperactivity disorder (2016)
Introduction: In a previous study carried out with children from first to third grade in an elementary school, the authors of this research evidenced that different profiles of neuropsychological difficulties and functional status of brain structures exist at subcortical and cortical levels. Such results differ from those obtained in preschool children.Objective: To correlate data obtained through neuropsychological assessment and EEG in Mexican children from fourth grade through sixth grade in an elementary school diagnosed with ADHD.Materials and methods: A qualitative syndromic analysis was used to establish predominant neuropsychological mechanisms. A qualitative analysis of EEG was conducted to determine functional and maturational aspects of children’s development.Results: Findings of correlations between neuropsychological and electrophysiological data showed diversity of neuropsychological difficulties and specific EEG patterns. The possibility of high correlation between data of qualitative neuropsychological analysis and functional analysis of electroencephalographic phenomenon is discussed.Conclusions: Final results suggest an important predictive level regarding clinical profiles obtained through the joined work of the clinical qualitative instruments used in this study.